Commercial drones can provide accurate and effective monitoring of the world's rarest primate - Hui Zhang; Samuel T. Turvey; Shree P. Pandey; Xiqiang Song; Zhongyu Sun; Nan Wang (Remote Sensing in Ecology and Conservation, 2023)
Abstract The recently established Hainan Tropical Rainforest National Park has designated the Hainan gibbon (Nomascus hainanus) as its flagship species, providing new hope for recovery of the last surviving population of the world's rarest primate. However, current monitoring methods are labour‐intensive and only conducted for discrete periods, meaning that detailed information is still lacking on key Hainan gibbon population parameters (such as movement patterns, sleeping site selection and home range size). Alternative monitoring techniques are therefore necessary to supplement traditional methods and provide more accurate estimates of population parameters. Here, we tested whether flying two drones (DJI MAVIC2 Enterprise Advanced), one in the understory and the other above the canopy, could provide new information on Hainan gibbon biology and ecology. During a total of 60 flights, we successfully collected clear RGB and thermal infrared footage of Hainan gibbons. These data provide new baseline information on gibbon movement within the understory and the canopy, their surface body temperatures (23.0–34.7°C), and their movement area during the survey period. The low cost of this equipment could reduce the running costs for Hainan gibbon monitoring. Although drone‐based monitoring has some limitations (e.g. monitoring efficiency could be affected by variation in forest structure and gibbon group size), this new method could complement existing monitoring approaches. Drone‐based monitoring, using multiple drones and a real‐time transmission network, could therefore contribute further towards Hainan Tropical Rainforest National Park's conservation planning for this Critically Endangered primate.